Study of The Factors That Influence Brand Loyalty Simpati Cards PT. Telkomsel Tbk - Mahadi Pardede; Vanessa Gaffar; Hilda Monoarfa (Westscience Press, 2024)
Customer loyalty is critical for success in today's saturated mobile telecommunications industry. However, maintaining allegiance remains challenging given technology advancements and intensifying competition. This study examines the determinants of loyalty towards Simpati, the prepaid brand of Indonesia's largest operator Telkomsel. A qualitative case study methodology was employed, comprising an extensive literature review on customer experience, satisfaction, trust, switching costs and their influence on brand loyalty in the mobile sector. Particular focus was placed on publications related to Telkomsel and its prepaid offerings. Customer data from secondary sources was also analyzed to identify patterns relating to the research objectives. The findings indicate that service quality is a key antecedent of customer experience and satisfaction. Superior fulfillment of expectations cultivates a positive brand image and drives attachment. Meanwhile, affective factors like emotional engagement and trust act as mediators reinforcing loyalty intentions over the long-term. Competitive pricing and targeted promotional campaigns also enhance perceived value. Additionally, high perceived switching costs curb defection propensity due to customers' sunk investments in the relationship.